TREATMENT AND TREATMENT FEATURES OF ENT DISEASES IN PREGNANT WOMEN - Tillabayeva Dilnoza Murodovna; Umarova Surayyo Khairullayevna (Western European Studies, 2025)
Pregnancy is accompanied by physiological immunosuppression and hormonal changes, which predispose women to diseases of the ear, nose, and throat (ENT). This article discusses the most common ENT pathologies typical of the gestational period and outlines modern approaches to diagnosis and treatment, taking into account the safety of both mother and fetus.
Keywords: pregnancy; pregnancy rhinitis; sinusitis